Language Barriers to Gender Equity in Senior Executive Leadership - Stryker, Susan R. (Journal of Management Policy and Practice, 2018)
The impact of cultural forces such as language is powerful in understanding the culture of an organization as language operates outside of an individual’s general awareness. Understanding how language is used by executive leaders can lend a significant insight into language usage that may promote member integration into the executive culture. This study has conducted a comparative quantitative analysis of the language of women and men executives who have succeeded in the roles as CEOs.